Pressure Wave Elimination in Iraqi Crude Oil Pipelines Using Novel Porous Filter and Electronic Control System - I. Ibrahim, Raheek; K. Odah, Manal; S. Salman, Hawraa (International Journal of Engineering and Technology, 2018)
The pressure wave is a serious problem in crude oil transportation pipelines. It is generated at the beginning and at the end of crude oil pumping process or as a result of sudden closing of valves. The high turbulence fluid particles in presence of pressure wave resulting in sever stresses on pipe walls needing for maintenance and replacement after a period of time. It is also leading to dissipation of flow energy consuming much more power for oil pumping. The objective of the present work is to decrease and eliminate the pressure wave in Iraqi crude oil pipelines through designing, manufacturing, and testing of a novel pressure wave filter with optimum design. The experimental system consists from: porous filter, oil pipe, pump, AC drive, and digital pressure transducers. The porous filter that was tested to eliminate the pressure wave is composed from various pipes (0.5 inch Perspex pipe, 1 inch PVC pipe, and 2 inches stainless steel pipe) with different porous materials to absorb the pressure energy from the fluid particles. These porous media are (1.5cm, 1cm, 0.4cm glass beads, and glass cylinders of 2cm length, 2cm outer diameter, and 2mm thickness). The experimental results proved the successful of the invented porous filter for eliminating the pressure wave by 99% using optimum design without suppressing the flow rate of crude oil in the pipe. The results obtained are quite significant since it awards a simple and low-cost solution for a real and practical problem in crude oil transportation sector.Â